Answer: y = - x + 1
Step-by-step explanation:
For us to write the equation for this line, we need to (1) find the slope of the line, and (2) use one of the points to write an equation:
The question gives us two points, (-3, 4) and (2, -1), from which we can find the slope and later the equation of the line.
Finding the Slope
The slope of the line (m) = (y₂ - y₁) ÷ (x₂ - x₁)
= (4 - (- 1)) ÷ ((-3) - 2)
= - 1
Finding the Equation
We can now use the point-slope form (y - y₁) = m(x - x₁)) to write the equation for this line:
⇒ y - (-1) = - 1 (x - 2)
y + 1 = - (x - 2)
we could also transform this into the slope-intercept form ( y = mx + c) by making y the subject of the equation:
since y + 1 = - (x - 2)
∴ y = - x + 1
To test my answer, I have included a Desmos Graph that I graphed using the information provided in the question and my answer.